Anhedonia, positive affect dysregulation, and risk and maintenance of binge‐eating disorder. Issue 3 (9th December 2020) - Mason, Tyler B.; Smith, Kathryn E.; Anderson, Lisa M.; Hazzard, Vivienne M.
Abstract: Low positive affect has been identified as an antecedent of binge‐eating episodes among individuals with binge‐eating disorder (BED), yet positive affect has received far less attention in eating disorders research than its counterpart, negative affect. In this article, we argue that the low levels of positive affect which occur with anhedonia (i.e., loss of interest or pleasure in activities) may contribute to the onset and maintenance of BED. We introduce a theoretical model in which anhedonia increases the risk for BED through its interrelationships with dysregulated eating and weight gain, and we describe potential direct (e.g., reward‐related processes) as well as indirect (e.g., influences on depressive symptoms and physical activity) pathways by which anhedonia may lead to adverse eating‐ and weight‐related outcomes. We also propose a momentary maintenance model in which low positive affect and positive affect dysregulation occurring with anhedonia maintain binge eating directly and indirectly through maladaptive health behaviors, such as decreased physical activity, less healthy eating, and fewer social interactions, which in turn maintain anhedonia. We draw upon outside literature to present evidence that aligns with the proposed risk and maintenance models and conclude by outlining avenues for future research—including methodological/measurement, theoretical, and clinical research directions.